Long-term CIN3+ risk in women with abnormal cytology; role of hrHPV testing - Kocken, M (Nature Publishing Group, 2012)
BACKGROUND: Many studies have examined the short-term value of high-risk human papillomavirus (hrHPV) testing in predicting cumulative risk of cervical intraepithelial neoplasia grade 3 or cancer (CIN3+). This study focuses on long-term CIN3+ risk after initial wait and see policy. METHODS: A total of 342 women with abnormal cytology of borderline/mild dyskaryosis (BMD) or worse (>BMD), included between 1990 and 1992, were followed-up by cytology and hrHPV testing until 1996 and monitored by cytology thereafter. Primary endpoint was cumulative CIN3+ risk by December 2009. RESULTS: Women with BMD had a 5-year CIN3+ risk of 22.5% (95% confidence interval (CI) 17.0–29.1) and of 0.7% (0.1–4.5) in the subsequent 5 years. High-risk human papillomavirus-negative women with BMD had a 5-year risk of <0.01% (95% CI 0.0–5.1) and of <0.01% (0.0–5.7) in the following 5 years, while for hrHPV-positive women these risks were 37.5% (29.0–46.9) and 1.6% (0.2–9.5), respectively. Women with >BMD had a 5-year risk of 45.1% (36.4–54.1) and of 3.5% (0.9–12.2) in the subsequent 5 years. High-risk human papillomavirus-negative women with >BMD had a 5-year risk of 7.3% (2.0–23.6) and hrHPV-positive women of 56.6% (46.4–66.3). CONCLUSION: Women with BMD have an elevated CIN3+ risk for 5 years only; afterwards their risk is similar to the general population. High-risk human papillomavirus-negative women with BMD may return to regular screening directly. All other women with ⩾BMD should be referred for additional testing and/or colposcopy.